Histological and Cytoarchitectural Measurements of Human Epidermis in Different Anatomical Sites of Embryonic, Fetal and Neonatal Iraqi Subjects in Al-Hilla/Iraq Maternity Hospital - khalfa, Hydar muhsin; Albideri, Adnan; jaffat, Haider salih (Journal of pharmaceutical sciences and research, 2018)
Abstract The integumentary system covers the surface of the embryo (skin) and its specialized skin structures including hair, nails, sweat glands, mammary glands and teeth. Fresh tissues of all 4 sites from all ages were embedded in glutaraldehyde then processed with osmium tetroxide and a series of alcohol concentration according to manufacturer protocol before coated with gold and photographed using scanning electron microscope (SEM). Statistical analysis shows significance P < 0.05 between all values at all ages of gestation and sites expect for 6 months and neonatal where there is no statistical significance for the distance between hair follicles.